2022
DOI: 10.3847/1538-4357/ac8230
|View full text |Cite
|
Sign up to set email alerts
|

Timing Properties of the X-Ray Accreting Pulsar 1A 0535+262 Studied with Insight-HXMT

Abstract: We report results on the timing analysis of the 2020 giant outburst of 1A 0535+262, using broadband data from Insight-HXMT. The analysis of the pulse profile evolution from the subcritical-luminosity to the supercritical-luminosity regime is presented for the first time. We found that the observed pulse profile exhibits a complex dependence on both energy and luminosity. A dip structure at the energy of the cyclotron resonant scattering features is found for the first time in the pulse fraction–energy relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
20
2
Order By: Relevance
“…Apart from this transient feature, the pulse profiles do not show any appreciable luminosity dependence. This is contrary to several other sources (see, e.g., Klochkov et al 2008;Malacaria et al 2015;Epili et al 2017;Koliopanos & Vasilopoulos 2018;Wilson-Hodge et al 2018;Wang et al 2022), where a drastic change of the pulse profile is observed as a function of luminosity, and is interpreted as a change of the accretion column beaming pattern (Basko & Sunyaev 1976;Becker et al 2012;Mushtukov et al 2015b). Here, despite the probed outburst stages ranging from a bolometric luminosity of about 5 × 10 37 erg s −1 to a peak luminosity that is about 60% of the Eddington luminosity for a 1.4 M NS (see Fig.…”
Section: A Steady Pulse Profile and Pulsed Fractioncontrasting
confidence: 99%
“…Apart from this transient feature, the pulse profiles do not show any appreciable luminosity dependence. This is contrary to several other sources (see, e.g., Klochkov et al 2008;Malacaria et al 2015;Epili et al 2017;Koliopanos & Vasilopoulos 2018;Wilson-Hodge et al 2018;Wang et al 2022), where a drastic change of the pulse profile is observed as a function of luminosity, and is interpreted as a change of the accretion column beaming pattern (Basko & Sunyaev 1976;Becker et al 2012;Mushtukov et al 2015b). Here, despite the probed outburst stages ranging from a bolometric luminosity of about 5 × 10 37 erg s −1 to a peak luminosity that is about 60% of the Eddington luminosity for a 1.4 M NS (see Fig.…”
Section: A Steady Pulse Profile and Pulsed Fractioncontrasting
confidence: 99%
“…b Adopted from Sartore et al (2015). c Derived from Insight-HXMT observations (Wang et al 2022; see text).…”
Section: Discussionmentioning
confidence: 99%
“…For the 2011 outburst, we used the timing solution reported in Sartore et al (2015) derived using INTEGRAL observations. For the recent 2020 outburst, thanks to the extensive coverage of Insight-HXMT observations (Wang et al 2022), we used the phase-connection technique (Deeter et al 1981) to determine the spin evolution accurately. In practice, for each 1000 s segment we folded background-subtracted light curves in the energy range of 25-80 keV, for which the pulse profile shape is relatively stable.…”
Section: Timing Solutionsmentioning
confidence: 99%
“…Insight-HXMT (Zhang et al 2014(Zhang et al , 2020 performed a highcadence observational campaign and obtained unprecedented high-quality data of 1A 0535+026 during its giant outburst in 2020. In Figure 1 we show the observed evolution of the pulse profiles (adopted from Wang et al 2022), as a function of the bolometric luminosity of the source estimated using the broadband spectroscopy in the energy range of 2-150 keV and assuming a distance of 2 kpc. During the outburst, as reported by Wang et al (2022), the pulse profile shows a complex variation with energy and luminosity.…”
Section: Available Data and Data Selectionmentioning
confidence: 99%
“…Kong et al (2021) also reported significant differences in the observed broadband X-ray spectrum between the rising and fading phases of the outburst, suggesting a somewhat different emission region geometry even at the same accretion rate in two phases of the outburst. On the other hand, using Insight-HXMT observations, Wang et al (2022) reported the complex pulse profile evolution throughout the outburst, which exhibits a strong energy and luminosity dependence. Here we investigate observed variations of the pulse profile more quantitatively and apply the decomposition method by Kraus et al (1995) to Insight-HXMT data.…”
Section: Introductionmentioning
confidence: 99%